Formulation, designing and evaluation of gastro-retentive floating microspheres using silymarin, curcumin and piperine for hepatoprotection - Badewale, Misbah Sultana Abdul Kausar; Tegeli, Varsha Siddheswar (Journal of Applied Pharmaceutical Research, 2025)
Background: Curcumin, Silymarin, and Piperine are natural phytoconstituents with proven hepatoprotective effects; however, their therapeutic efficacy is limited by poor water solubility and low oral bioavailability. A gastro-retentive floating drug delivery system offers a strategic approach to enhance gastric residence time and improve absorption in the upper gastrointestinal tract. Methodology: Floating microspheres were developed using the solvent evaporation technique with Ethyl Cellulose and Eudragit RS 100 as polymers. A series of trial formulations was statistically optimized using Design Expert® software. The microspheres were evaluated for particle size, buoyancy, entrapment efficiency, drug release profile, and stability. Results and Discussion: The optimized formulation (Batch F3) demonstrated high encapsulation efficiency (>98%) and sustained buoyancy of 95.94% over 8-hour. At the end of 12 hours, cumulative drug release was 66.24% for Curcumin, 68.21% for Silymarin, and 72.82% for Piperine. Drug release followed zero-order kinetics, with the best model fit (R² = 0.9938) observed for Piperine. SEM images confirmed the presence of spherical and uniform microspheres. The formulation remained stable for 90 days under ICH Q1A(R2) conditions. Conclusion: The developed microspheres offer a promising gastroretentive system for controlled delivery of hepatoprotective agents, potentially improving therapeutic outcomes for liver-related disorders.